2022
DOI: 10.1007/s00289-022-04593-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ricinus communis shredded material as filler in rotational molded parts to improve the bio-disintegration behavior

Abstract: This paper focuses on the use of castor oil plant (Ricinus communis) as filler in rotomolded parts using polyethylene (PE) and polylactic acid (PLA) as polymer matrixes. The vegetable shredded material was used in 5 and 10% weight following a dry blending procedure and then rotomolded to obtain cube test parts. This material was characterized to determine its chemical composition, thermal stability, and structure. The NaOH-treated material shows reduced hemicellulose content and higher thermal stability. Obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…A lack of modulus change recorded by Andrzejewski et al upon tensile testing, was thought to be due to high porosity and PLA/BH composites’ increase in brittle behaviour. Other studies reported on the use of valorised Ricinus communis particles in PE and PLA, communicating significant reductions in impact strength when exceeding 5 wt% and reductions in tensile strength in PE, but some increased in PLA [ 71 ]. Robledo-Ortiz et al [ 46 ] noticed poor compatibility between bio-based PE and natural fillers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of modulus change recorded by Andrzejewski et al upon tensile testing, was thought to be due to high porosity and PLA/BH composites’ increase in brittle behaviour. Other studies reported on the use of valorised Ricinus communis particles in PE and PLA, communicating significant reductions in impact strength when exceeding 5 wt% and reductions in tensile strength in PE, but some increased in PLA [ 71 ]. Robledo-Ortiz et al [ 46 ] noticed poor compatibility between bio-based PE and natural fillers.…”
Section: Resultsmentioning
confidence: 99%
“…• Applying chemical treatment using GMA-g-PLA, fibre-matrix interfacial adhesion was improved and porosity was reduced • At 25 wt% with fibres treated twice, improvements were recorded in flexural and tensile properties compared to neat PE [71] PE, PLA Ricinus Cummunis Particles…”
Section: Biopolymers and Biocompositesmentioning
confidence: 99%
“…where ∆H 0 is the enthalpy for 100% crystalline sample (293 J/g for PE [52]), and m Sp is the mass fraction of the microalgae. The oxidation induction time (OIT) of the composite materials was also determined by DSC following the UNE-EN ISO 11357-6:2018 standard [53].…”
Section: Thermal Behaviormentioning
confidence: 99%